2004
DOI: 10.1093/molehr/gah104
|View full text |Cite
|
Sign up to set email alerts
|

AZF and DAZ gene copy-specific deletion analysis in maturation arrest and Sertoli cell-only syndrome

Abstract: Deletions of the AZFc region in Yq11.2, which include the DAZ gene family, are responsible for most cases of male infertility and were associated with severe oligozoospermia and also with a variable testicular pathology. To uncover the functional contribution of DAZ to human spermatogenesis, a DAZ gene copy-specific deletion analysis was previously established and showed that DAZ1/DAZ2 deletions associate with oligozoospermia. In this study we applied the same screening method to 50 control fertile males and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 33 publications
3
36
2
3
Order By: Relevance
“…14 genes are protein-coding and 17 represent non-proteincoding transcripts [8][9][10] . Although there is still no definitive consensus about the relationship between the type of microdeletion and the resulting sperm defect, microdeletions in AZFa lead mostly to Sertoli cell-only syndrome, mutations in AZFb provoke an interruption in meiosis I, and mutations in AZFc result in hypospermatogenesis, progressing to severe azoospermia or oligospermia [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…14 genes are protein-coding and 17 represent non-proteincoding transcripts [8][9][10] . Although there is still no definitive consensus about the relationship between the type of microdeletion and the resulting sperm defect, microdeletions in AZFa lead mostly to Sertoli cell-only syndrome, mutations in AZFb provoke an interruption in meiosis I, and mutations in AZFc result in hypospermatogenesis, progressing to severe azoospermia or oligospermia [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…There have been several conflicting reports about the association between KFS and AZF microdeletions (Ambasudhan et al, 2003;Ferrás et al, 2004;Foresta et al, 2005;Mitra et al, 2006;Arruda et al, 2007;Choe et al, 2007;Ceylan et al, 2010;Behulova et al, 2011). Accordingly, analysis and comparison with other studies of these associations is justified.…”
Section: Discussionmentioning
confidence: 99%
“…It was later found that microdeletions of four subregions of the AZF region (AZFa, AZFb, AZFc, and AZFd) led to various types of spermatogenesis impairments, from teratozoospermia to infertility, with different population distributions depending on their Y haplogroup profile (Li et al, 2008;Wang et al, 2010). For example, microdeletions in AZFa led mostly to Sertoli cell-only syndrome, mutations in AZFb resulted in an arrest of spermatogenesis at meiosis I, and mutations in AZFc were associated to hypospermatogenesis with progression to severe azoospermia or oligospermia (Ferrás et al, 2004;Foresta et al, 2005;Zhou et al, 2006;Arruda et al, 2007;Wang et al, 2010;Behulova et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…The presence of different stages of spermatogenic cells in the testis can be confirmed by the detection of certain mRNAs, exclusively expressed at a relevant maturation level [Matzuk and Lamb 2008]. Recently, highly specific cellular and molecular methods such as flow cytometry [Koscinski et al 2005] and Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) [Bauer and Patzelt 2003;Ferras et al 2004;Patrizio et al 2000;Song et al 2000] have been used to detect germ cells in the testis. However, molecular methods are mainly based on detecting testis specific transcripts in testicular biopsies rather than seminal fluid.…”
Section: Introductionmentioning
confidence: 99%